A syringe-like love dart injects male accessory gland products in a tropical hermaphrodite - Joris M. Koene; Menno Schilthuizen; Liew, Thor Seng; Kora Montagne-Wajer (Public Library Science, 2013)
Sexual conflict shapes the evolution of many behaviours and processes involved in reproduction. Nearly all evidence supporting t his comes from species where the sexes are separated. However, a substantial proportion of animals and most plants are hermaphroditic, and theoretical work predicts that sexual conflict plays an important role even when the sexes are joined within one individual. This seems to have resulted in bizarre mating systems, sophisticated sperm packaging and complex reproductive morphologies. By far the best-known example of such a strategy in hermaphrodites is the shooting of so-called love-darts in land snails. All known love darts carry a gland product on their outside and enter this into the partner’s hemolymph by stabbing. Here, we show that species of the snail genus Everettia possess a syringe-like dart that serves as a real injection needle. Their dart is round in cross-section, contains numerous channels, and has perforations along its side. Histology and electron microscopy show that these holes connect to the channels inside the dart and run all the way up to the elaborate mucus glands that are attached to the dart sac. This is the first report on a love dart that is used as a syringe to directly inject the gland product into the partner’s hemolymph. Although the exact use and function of this dart remains to be demonstrated, this clearly adds to the complexity of the evolution of reproductive strategies in hermaphrodites in general. Moreover, the perforations on the outside of the love dart resemble features of other injection devices, thus uncovering common design and repeated evolution of such features in animals.